Peningkatan Proses Pembelajaran Tematik Terpadu Menggunakan Model Problem Based Learning - Nanda, Mulia; Mansurdin, Mansurdin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2021)
The objective of this research is to describe an integrated thematic learning process improvement to the model of problem based learning in fourth grade elementary school 15 Ulu Gadut Padang City. The approach used in this research is qualitative and quantitative. The research aspects of the teacher first cyclethe average value of 84% with good qualification, in the second cycle to 93% with excellent qualifications. Aspects of the students' first cycle the average value of 84% with good qualification,in the second cycle to 93%, with excellent qualifications. Thus the model of problem based learning can enhance the learning process and student learning outcomes.